THE EFFECTS OF TASK INDUCED INVOLVEMENT LOAD HYPOTHESIS ON TURKISH EFL LEARNERS’ INCIDENTAL VOCABULARY LEARNING - Yorgancı, Mehtap; Subaşı, Gonca (International Online Journal of Education and Teaching, 2022)
Recently vocabulary studies have mainly focused on two forms of vocabulary acquisition: incidental and intentional vocabulary acquisition. For incidental vocabulary acquisition, Task-induced Involvement Load Hypothesis was put forward by Hulstijn and Laufer (2001) to investigate the vocabulary tasks by comparing their levels of involvement load to each other. To test this hypothesis, the current study utilized six different vocabulary tasks with varying levels of involvement load. On the other hand, in order to investigate the task type effect, each task with another task from the other task type group was compared. The last part of the study was designed specially to test the task type effect which was neglected by the hypothesis as the hypothesis suggested that only involvement load levels affect the results. The findings concluded that different involvement load levels yielded varying results most of which provided support for the hypothesis. However, task types did not provide evidence in favour of the hypothesis by not leading to similar results for the tasks who shared the same involvement load index. The study concluded with some pedagogical implications and suggestions for further studies. Keywords: incidental vocabulary acquisition, TILH, Task-induced Involvement Load Hypothesis, Turkish EFL prep students, vocabulary task type effect